Inventing Great Neck : Jewish Identity and the American Dream - Goldstein, Judith S. (Book collections on Project MUSE., 2006)
Great Neck, New York, is one of America?s most fascinating suburbs. Since the mid-nineteenth century, generations have been attracted to this once quiet enclave for its easy access to New York City and its tranquil setting by the Long Island Sound. It became an illustrious suburb, home to numerous film and theatrical luminaries, among them Groucho Marx, Eddie Cantor, Oscar Hammerstein II, and Alan King. Famous writers who lived there include Ring Lardner and, of course, F. Scott Fitzgerald, who used Great Neck as the inspiration for his classic novel The Great Gatsby. Although frequently recog.